Pengetahuan Keluarga dan Kesinambungan Penanganan Anak dengan Autism Spectrum Disorder di Rumah - Zurriyatun Thoyibah; Haryani; Sri Hardiani (LPPM STIKES Marendeng Majene, 2026)
Autism Spectrum Disorder (ASD) is a neurological disorder affecting cognitive, emotional, and psychomotor functions, commonly found in children. Successful management of autism relies on the role of the family, supported by their knowledge regarding home-based care. This study aimed to analyze the relationship between family knowledge and the continuity of home-based care for children with ASD. This quantitative study employed a cross-sectional design and involved 36 families of children with ASD attending the MSC Clinic at Mutiara Sukma Psychiatric Hospital, selected via purposive sampling. Data were collected using questionnaires assessing autism knowledge and the continuity of care. Chi-square test results indicated that while the majority of respondents possessed good knowledge (69.4%), the implementation of home-based care fell mostly into the